Severe pneumonia caused by Nocardia otitidiscaviarum in a patient with bronchiectasis and IgA nephropathy: a case report - Lin, Yi; Jiang, Zhao-Zhao; Chi, Xiao-Qian; Chen, Jian-Sheng; Wen, Chao; Zhang, Chao; Wang, Ying-Ying; Xie, Guang-Liang (Frontiers in Medicine, 2025)
BackgroundNocardia species are rare opportunistic pathogens in the clinic, with strong invasiveness and dissemination, that can cause serious pulmonary infection, especially in immunocompromised patients, chronic lung diseases and hormone use, and is easy to be missed and misdiagnosed, preventing patients from obtaining timely and effective treatment, resulting in a high mortality rate.Case presentationHere, we present a rare case of a patient with chronic bronchiectasis and IgA nephropathy who developed Nocardia otitidiscaviarum pneumonia shortly after hormone therapy. The patient presented with tongue and lip ulcers, chest distress, cough, expectoration, and fever as the initial symptoms, which were extremely similar to common bacterial pulmonary infections. The laboratory examination and pulmonary computer tomography results indicated pulmonary infection, but the blood and multiple sputum cultures failed to identify the pathogen. Empirical treatment with piperacillin/tazobactam sodium and ceftriaxone was ineffective, and the patient’s condition worsened and progressed to respiratory failure. Subsequently, a bronchoscopy examination was performed, and the bronchoalveolar lavage fluid was collected for bacterial culture, which indicated Nocardia infection, however the treatment used of trimethoprim-sulfamethoxazole combined with imipenem was not effective. Finally, the patient was confirmed to have Nocardia otitidiscaviarum infection by mass spectrometry. According to the antibiotic sensitivity test and minimum inhibitory concentration (MIC) value results, Nocardia otitidiscaviarum was resistant to imipenem, so the treatment was changed to trimethoprim-sulfamethoxazole combined with linzolid. The patient’s condition improved rapidly and he was discharged after his condition was stable.ConclusionThis case reminded us that for patients with a history of chronic lung disease, when pulmonary infection occurs during hormone or immunosuppressive therapy for kidney disease, the possibility of Nocardia infection should be fully considered, and high-quality specimens should be collected as early as possible. Appropriate bacterial culture methods and efficient identification techniques should be adopted to promptly identify pathogens, and personalized treatment plans should be developed based on antibiotic sensitivity tests to save patients’ lives.